THE PATTERN OF PSYCHIATRIC MORBIDITY IN ATTENDEES OF A DERMATOLOGY CLINIC - Bashir, Khalid; Rana, Mowadat Hussain (Pakistan Armed Forces Medical Journal, 2006)
Background: The purpose of the study was to document the prevalence and pattern of psychiatric morbidity in dermatology outpatient clinics and to identify the risk factors for development of psychiatric disorders in patients with skin diseases. Study Design: Descriptive study. Patients and Methods: A random sample of one hundred and fourteen patients attending Out Patient Department (OPD) of Dermatology at C.M.H Lahore was screened for psychiatric complaints by using Urdu version of General Health Questionnaire – 12. Patients scoring “two” and above on GHQ-12 were selected for the stage two interview based on Present State Examination. The final diagnosis was on criteria of International Classification of Diseases – 10. Those who had no diagnosable psychiatric illness were placed in non-ill or group “N”. Those scoring ≥ 2 on GHQ - 12 and confirmed to have psychiatric morbidity on clinical interview by a psychiatrist were placed in ill group “D”. Results: Out of 114 patients having dermatological disorders, 39 (34.11%) had psychiatric morbidity. Amongst psychiatric disorders depression was seen in 25 (21.9%), and Anxiety in 11 (9.64%), other diagnoses are uncommon. Commonest psychological symptoms reported by patients are loss of interest, reduced self-esteem, tendency to avoid people, depressed mood, disturbed sleep and ideas of self-harm. Extensive skin lesions on the exposed parts of the body and more than six months duration of skin complaints were major risk factors for psychiatric illness. Patients with chronic disfiguring lesions like acne, eczema, psoriasis and vitiligo have more chances to develop psychiatric morbidity. Conclusion: It is concluded that one-third of dermatology patients have significant psychiatric morbidity and with little training dermatologists can reliably identify psychiatric morbidity by simple inquiry and use of GHQ – 12, as screening instrument, which can be helpful in early detection and management of psycho-dermatological disorders.